Characterization of wheat lacking B-type starch granules. (March 2022) - Saccomanno, Benedetta; Berbezy, Pierre; Findlay, Kim; Shoesmith, Jennifer; Uauy, Cristobal; Viallis, Bruno; Trafford, Kay
Abstract: The physicochemical and agronomic properties of a new form of bread wheat lacking B-type starch granules (BlessT) were assessed. Three BlessT mutant lines made by combining homoeologous deletions of BGC1, a gene responsible for the control of B-granule content, were compared with two sibling lines with normal starch phenotype and the parent line, cv. Paragon. Quantification of starch granule size and number in developing grain confirmed the lack of small, B-type starch granules throughout development in BlessT. Most starch, flour, grain and loaf characteristics did not vary between BlessT and the wild type sibling controls. However, BlessT starches had higher water absorption, reduced grain hardness and higher protein content, and dough made from BlessT flour required more water and had increased elasticity. Despite the lack of B-granules, BlessT lines do not display a significant decrease in total starch content suggesting that it should be possible to produce commercial wheat varieties that lack B-type starch granules without compromising yield. These findings support the potential utility of this novel type of wheat as a specialist crop in applications ranging from bread making and alcohol production to improved industrial starch products. Graphical abstract: Image 1 Highlights: BlessT lines lack small, B-type starch granules throughout grain development. BlessT starches have higher water absorption, reduced grain hardness and higher protein content. BlessT flours do not display a significant decrease in total starch content.